Morphological prerequisites for the formation of fascial duplication in the elimination of damage to the anterior rectal wall during prostatectomy - Yu. N. Yurgel; B. Ya. Alekseev; E. I. Kopyltsov; O. V. Leonov; I. A. Sikhvardt; A. O. Leonova; S. S. Stepanov; S. A. Koroleva (Инновационная медицина Кубани, 2021)
Background Intraoperative rectal injury in prostatectomy patients is an uncommon but severe complication. Particular attention is paid to improving the results of healing damage to the anterior rectal wall during prostatectomy.Objective To study the morphological features of the parietal pelvic fascia and the rectal wall to substantiate the possibility of the formation of fascial duplication in the elimination of damage to the anterior rectal wall during prostatectomy.Material and Methods The authors carried out an intravital morphological analysis of the parietal pelvic fascia covering the levator rectum muscle and the anterior rectal wall in 10 men.Results The parietal pelvic fascia contains more powerful bundles of collagen fibers, which in certain areas are partially woven into the fibers of striated muscle tissue. The adventitia of the rectum is characterized by a looser arrangement of the interacting components of the formed connective and smooth muscle tissue. In the studied formations of the small pelvis, the thickness of collagen fibers separately and in the composition of bundles, as well as the cells of the differon and each fiber separately did not differ, which indicated the identity of their tinctorial properties in the compared zones.Conclusion Morphological analysis showed that when juxtaposing and touching the edges of the healing area of the surgical wound without tension, a stable and continuous scar of the fascial duplication is formed, which ensures reliable fusion of the stitched anatomical structures.